Pemerolehan Bahasa Anak Usia 3 Tahun pada Tataran Fonologi: Kajian Psikolinguistik - Putri, Meysi Anisa; Awwalinda, Nisa; Fatmawati, Fatmawati (UIR Press, 2025)
This study aims to describe the process of language acquisition in a 3-year-old child, focusing on phonological development, using a qualitative approach. Data were collected from recorded conversations and observations of the research subject, Angkasa Dexano Nugraha. A narrative analysis method was used to explore the variations in sounds produced, as well as phoneme omissions and substitutions that occurred. The results showed that Angkasa was able to produce significant sound variations, although phoneme omissions often occurred, such as the substitution of /k/ with /t/ in the word